Exploring the professional experiences of english language learner high school teachers in a rural state: A qualitative investigation - Gilblom, Elizabeth A.; Crary, Sarah L.; Wiltse, Stacey E. (American Journal of Education and Learning, 2025)
The purpose of this research was to explore the perceptions and experiences of high school teachers in North Dakota who teach English Language Learners (ELL). Using the transcendental phenomenological method, we interviewed seven teachers with between 10 and 23 years of experience working with ELL students. Ecological systems theory (EST) was employed to capture specific elements and processes present in the school environment that assist or hinder ELL teachers as they fulfill their work responsibilities and support the resettlement of New Americans. The findings revealed the complex and multifaceted role of ELL teachers, which is affected by multiple ecological factors and duties that extend well beyond teaching in a classroom. Participants felt supported in their work life by ELL teachers, paraeducators, interpreters, and ELL programs. However, the participants expressed aspects of their work lives that inhibit their ability to assist ELL students, including the exclusive responsibility of ELL, a lack of professional development opportunities, time-consuming language testing responsibilities, and conflicts with mainstream teachers who do not fully understand how to best engage with ELL students. In light of these findings, we offer practical implications for schools to better support ELL teachers and foster inclusive school environments for English learners and New Americans.